Attitude toward conflict and family business succession. - Salim, Linda; Mohd Shariff, Mohd Noor; Ahmad Arshad, Darwina (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2016)
Conflict is central in family business. Family business consists of family members working together, using family and business logics. Efforts are done to mitigate the impact of role conflicts. Nevertheless, conflict remains the top reason for discontinuity. Findings suggested that participants with positive attitude toward conflict take more relaxed approach toward succession, with larger next generation talent pool. This group is egalitarian in strategic decision making and characteristically optimistic. Participants with negative attitude have a smaller talent pool for succession, since they reserve leadership for the select few. They are more cautious, requiring successors to implement their visions beforehand, and are less optimistic. This study contributes to the body of knowledge and family business practitioners. Firstly, this paper introduces the use of attitude toward conflict to predict behaviour during succession. Secondly, this paper inspires leaders to assess their attitudes, and if required to change their attitudes, so that they can plan their succession accordingly.